RELATIONSHIP BETWEEN RAINFALL AND INCIDENCE OF LOCAL DISEASES IN SI SA KET PROVINCE - ฉัตรภูติ, ฉัตรสิริ; ชยธวัช, วัฒนา (Primary Health Care Journal (Northeastern Edition), 2025)
Infectious diseases associated with the rainy season, such as hand–foot–mouth disease, melioidosis, leptospirosis, and mushroom poisoning, tend to increase during the rainy months. However, there has been no prior quantitative investigation into the relationship between rainfall and the incidence of these diseases. This correlational study aimed to analyze the association between the average monthly rainfall and the number of patients with rainy season–related diseases, as well as to calculate the risk increment for each disease with a 1-millimeter increase in rainfall. Data were collected from the Disease Surveillance System 506 for patient information and from the National Water Data Repository for rainfall records spanning January 2018 to July 2024. The analyses were conducted using Pearson correlation statistics and the Generalized Linear Model (GLM). The study findings revealed that rainfall is moderately positively correlated with the incidence of mushroom poisoning (r = 0.603, p-value < .001) and weakly positively correlated with hand–foot–mouth disease (r = 0.326, p-value =.003). No statistically significant correlations were observed for melioidosis or leptospirosis. Furthermore, the risk of mushroom poisoning increased by approximately 1% for each 1-millimeter increment in average daily rainfall (IRR = 1.01, 95% CI: 1.008–1.012, p-value < .001). Conclusion, the results indicate that rainfall is significantly associated with the incidence of both mushroom poisoning and hand–foot–mouth disease in Si Sa Ket Province. These findings may serve as a basis for forecasting disease outbreaks and for planning preventive measures against infectious diseases related to the rainy season.